O-030 Perioperative complications with the Pipeline Embolisation Device: Predictive value of the P2Y12 Test. (14th July 2013) - Chalouhi, N; Ho, S; Jabbour, P; Starke, R; Tjoumakaris, S; Dumont, A; Rosenwasser, R; Gonzalez, L
Abstract : Background and Purpose: Dual anti-platelet therapy is necessary prior to treatment with the Pipeline Embolisation Device (PED). Although not fully accepted, routine monitoring of antiplatelet medications has been recently emphasised. The purpose of this study was to assess whether the P2Y12 test was predictive of perioperative complications with the PED and to identify an optimal pre-procedure value range. Methods: Sixty-seven patients treated with the PED at our institution were included for analysis. Patients received 81 mg of aspirin and 75mg of clopidogrel for 5–10 days prior to the procedure. P2Y12 receptor inhibition was assessed with the VerifyNow test (Accumetrics, San Diego, California). Results: All patients were on dual antiplatelet therapy and were tested on the day of the procedure. Mean aneurysm size was 10.4 mm, and mean number of PEDs was 1.4 per patient. Two patients were clopidogrel non responders and were switched to prasugrel before the procedure. The mean of the P2Y12 reaction units (PRU) was 148 ± 83 and the mean of the percentage inhibition was 51 ± 26. Perioperative complications (including clinically silent events) occurred in 11 (16.4%) patients (2 hemorrhagic and 9 ischaemic events). No patient had post-treatment aneurysm rupture and no PED thrombosed within 120 days. Patients with a percentage inhibition of ≤70 had a complication rate of 23% versus 0% in those with a percentage inhibition >70 (p=0.1). The complication rate tended to be lower in patients with PRU < 90 (5%) versus those with PRU ≥90 (20%, p=0.1). PRU was significantly predictive of the percentage inhibition via linear regression (p<0.001) with an overall formula: Percentage inhibition = 93.82 + (PRU x -0.286). Conclusion: A percentage inhibition of ≤70 and a PRU ≥90 tended to be associated with perioperative complications. Both parameters appear to be important for monitoring platelet function. Our results suggest that neurointerventionalists should target a percentage inhibition >70 for PED procedures. Further study is needed to determine the percentage inhibition above which the risk of hemorrhagic complications is increased. Disclosures: N. Chalouhi: None. S. Ho: None. P. Jabbour: None. R. Starke: None. S. Tjoumakaris: None. A. Dumont: None. R. Rosenwasser: None. L. Gonzalez: None.